Step 1
Given;
![4x^2-y^2+24x+4y+28=0](https://tex.z-dn.net/?f=4x%5E2-y%5E2%2B24x%2B4y%2B28%3D0)
Required; To find the center that eliminates the linear terms
Step 2
![\begin{gathered} 4x^2-y^2+24x+4y=-28 \\ 4x^2+24x-y^2+4y=-28 \\ Complete\text{ the square }; \\ 4x^2+24x \\ \text{use the form ax}^2+bx\text{ +c} \\ \text{where} \\ a=4 \\ b=24 \\ c=0 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%204x%5E2-y%5E2%2B24x%2B4y%3D-28%20%5C%5C%204x%5E2%2B24x-y%5E2%2B4y%3D-28%20%5C%5C%20Complete%5Ctext%7B%20the%20square%20%7D%3B%20%5C%5C%204x%5E2%2B24x%20%5C%5C%20%5Ctext%7Buse%20the%20form%20ax%7D%5E2%2Bbx%5Ctext%7B%20%2Bc%7D%20%5C%5C%20%5Ctext%7Bwhere%7D%20%5C%5C%20a%3D4%20%5C%5C%20b%3D24%20%5C%5C%20c%3D0%20%5Cend%7Bgathered%7D)
![\begin{gathered} consider\text{ the vertex }form\text{ of a }parabola \\ a(x+d)^2+e \\ d=\frac{b}{2a} \\ d=\frac{24}{2\times4} \\ d=\frac{24}{8} \\ d=3 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20consider%5Ctext%7B%20the%20vertex%20%7Dform%5Ctext%7B%20of%20a%20%7Dparabola%20%5C%5C%20a%28x%2Bd%29%5E2%2Be%20%5C%5C%20d%3D%5Cfrac%7Bb%7D%7B2a%7D%20%5C%5C%20d%3D%5Cfrac%7B24%7D%7B2%5Ctimes4%7D%20%5C%5C%20d%3D%5Cfrac%7B24%7D%7B8%7D%20%5C%5C%20d%3D3%20%5Cend%7Bgathered%7D)
![\begin{gathered} Find\text{ the value of e using }e=c-\frac{b^2}{4a} \\ e=0-\frac{24^2}{4\times4} \\ e=0-\frac{576}{16}=-36 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20Find%5Ctext%7B%20the%20value%20of%20e%20using%20%7De%3Dc-%5Cfrac%7Bb%5E2%7D%7B4a%7D%20%5C%5C%20e%3D0-%5Cfrac%7B24%5E2%7D%7B4%5Ctimes4%7D%20%5C%5C%20e%3D0-%5Cfrac%7B576%7D%7B16%7D%3D-36%20%5Cend%7Bgathered%7D)
Step 3
Substitute a,d,e into the vertex form
![\begin{gathered} a(x+d)^2+e \\ 4(x+_{}3)^2-36 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20a%28x%2Bd%29%5E2%2Be%20%5C%5C%204%28x%2B_%7B%7D3%29%5E2-36%20%5Cend%7Bgathered%7D)
![\begin{gathered} 4(x+3)^2-36-y^2+4y=-28 \\ 4(x+3)^2-y^2+4y=\text{ -28+36} \\ \\ \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%204%28x%2B3%29%5E2-36-y%5E2%2B4y%3D-28%20%5C%5C%204%28x%2B3%29%5E2-y%5E2%2B4y%3D%5Ctext%7B%20-28%2B36%7D%20%5C%5C%20%20%5C%5C%20%20%5Cend%7Bgathered%7D)
Step 4
Completing the square for -y²+4y
![\begin{gathered} \text{use the form ax}^2+bx\text{ +c} \\ \text{where} \\ a=-1 \\ b=4 \\ c=0 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%5Ctext%7Buse%20the%20form%20ax%7D%5E2%2Bbx%5Ctext%7B%20%2Bc%7D%20%5C%5C%20%5Ctext%7Bwhere%7D%20%5C%5C%20a%3D-1%20%5C%5C%20b%3D4%20%5C%5C%20c%3D0%20%5Cend%7Bgathered%7D)
![\begin{gathered} consider\text{ the vertex }form\text{ of a }parabola \\ a(x+d)^2+e \\ d=\frac{b}{2a} \\ d=\text{ }\frac{4}{2\times-1} \\ d=\frac{4}{-2} \\ d=-2 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20consider%5Ctext%7B%20the%20vertex%20%7Dform%5Ctext%7B%20of%20a%20%7Dparabola%20%5C%5C%20a%28x%2Bd%29%5E2%2Be%20%5C%5C%20d%3D%5Cfrac%7Bb%7D%7B2a%7D%20%5C%5C%20d%3D%5Ctext%7B%20%7D%5Cfrac%7B4%7D%7B2%5Ctimes-1%7D%20%5C%5C%20d%3D%5Cfrac%7B4%7D%7B-2%7D%20%5C%5C%20d%3D-2%20%5Cend%7Bgathered%7D)
![\begin{gathered} Find\text{ the value of e using }e=c-\frac{b^2}{4a} \\ e=0-\frac{4^2}{4\times(-1)} \\ \\ e=0-\frac{16}{-4} \\ e=4 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20Find%5Ctext%7B%20the%20value%20of%20e%20using%20%7De%3Dc-%5Cfrac%7Bb%5E2%7D%7B4a%7D%20%5C%5C%20e%3D0-%5Cfrac%7B4%5E2%7D%7B4%5Ctimes%28-1%29%7D%20%5C%5C%20%20%5C%5C%20e%3D0-%5Cfrac%7B16%7D%7B-4%7D%20%5C%5C%20e%3D4%20%5Cend%7Bgathered%7D)
Step 5
Substitute a,d,e into the vertex form
![\begin{gathered} a(y+d)^2+e \\ =-1(y+(-2))^2+4 \\ =-(y-2)^2+4 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20a%28y%2Bd%29%5E2%2Be%20%5C%5C%20%3D-1%28y%2B%28-2%29%29%5E2%2B4%20%5C%5C%20%3D-%28y-2%29%5E2%2B4%20%5Cend%7Bgathered%7D)
Step 6
![\begin{gathered} 4(x+3)^2-y^2+4y=\text{ -28+36} \\ 4(x+3)^2-(y-2)^2+4=-28+36 \\ 4(x+3)^2-(y-2)^2=-28+36-4 \\ 4(x+3)^2-(y-2)^2=4 \\ \frac{4(x+3)^2}{4}-\frac{(y-2)^2}{4}=\frac{4}{4} \\ (x+3)^2-\frac{(y-2)^2}{2^2}=1 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%204%28x%2B3%29%5E2-y%5E2%2B4y%3D%5Ctext%7B%20-28%2B36%7D%20%5C%5C%204%28x%2B3%29%5E2-%28y-2%29%5E2%2B4%3D-28%2B36%20%5C%5C%204%28x%2B3%29%5E2-%28y-2%29%5E2%3D-28%2B36-4%20%5C%5C%204%28x%2B3%29%5E2-%28y-2%29%5E2%3D4%20%5C%5C%20%5Cfrac%7B4%28x%2B3%29%5E2%7D%7B4%7D-%5Cfrac%7B%28y-2%29%5E2%7D%7B4%7D%3D%5Cfrac%7B4%7D%7B4%7D%20%5C%5C%20%28x%2B3%29%5E2-%5Cfrac%7B%28y-2%29%5E2%7D%7B2%5E2%7D%3D1%20%5Cend%7Bgathered%7D)
Step 7
![\begin{gathered} \frac{(x-h)^2}{a^2}-\frac{(y-k)^2}{b^2}=1 \\ \text{This is the }form\text{ of a hyperbola.} \\ \text{From here } \\ a=1 \\ b=2 \\ k=2 \\ h=-3 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%5Cfrac%7B%28x-h%29%5E2%7D%7Ba%5E2%7D-%5Cfrac%7B%28y-k%29%5E2%7D%7Bb%5E2%7D%3D1%20%5C%5C%20%5Ctext%7BThis%20is%20the%20%7Dform%5Ctext%7B%20of%20a%20hyperbola.%7D%20%5C%5C%20%5Ctext%7BFrom%20here%20%7D%20%5C%5C%20a%3D1%20%5C%5C%20b%3D2%20%5C%5C%20k%3D2%20%5C%5C%20h%3D-3%20%5Cend%7Bgathered%7D)
Hence the answer is (-3,2)
Answer:
I assume u have to use the phythag theory, so just omit the 45 and work out the 45 to prove its a right angle
Answer:
what grade
Step-by-step explanation:
.033220 divided by .16 = .20125
Answer:
-49
8
Step-by-step explanation:
-196/4 =
-49
(3+u)^2
-------------
8
Let u=5
(3+5)^2
-------------
8
(8)^2
-------------
8
64
-----
8
8